THE IMPLEMENTATION OF CHORAL AND REPEATED READING STRATEGY (CRRS) TO IMPROVE THE READING ABILITY OF YEAR 7 STUDENTS AT UPT SMPN 1 CEMPA PINRANG - Sri Nurhamdani; Chairil Anwar Korompot; Geminastiti Sakkir (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2023)
This research aims to determine the effectiveness of Choral and Repeated Reading Strategy (CRRS) in improving the reading ability of year 7 students at UPT SMPN 1 Cempa Pinrang. The cluster random sampling technique was used to select the sample of 28 students for this study. A reading test was an instrument in this study. After treatment, the results of this test were used to assess the Choral and Repeated Reading Strategy (CRRS) to improve the reading ability of year 7 students at UPT SMPN 1 Cempa Pinrang. It can be demonstrated that the t-test value was less than P (0.000 0.05), implying that the hypothesis (H0) of this study was rejected